Altered expression of acetylcholinesterase gene in rice results in enhancement or suppression of shoot gravitropism - Yamamoto, Kosuke (Plant Signal Behav, 2016)
Acetylcholinesterase (AChE), an acetylcholine-hydrolyzing enzyme, exists widely in plants, although its role in plant signal transduction is still unclear. We have hypothesized that the plant AChE regulates asymmetric distribution of hormones and substrates due to gravity stimulus, based on indirect pharmacological experiments using an AChE inhibitor. As a direct evidence for this hypothesis, our recent study has shown that AChE overexpression causes an enhanced gravitropic response in rice seedlings and suggested that the function of the rice AChE relates to the promotion of shoot gravitropism in the seedlings. Here, we report that AChE suppression inhibited shoot gravitropism in rice seedlings, as supportive evidence demonstrating the role of AChE as a positive regulator of shoot gravitropic response in plants.